Investigating the role of Caspase-1 in a mouse model of Juvenile X-linked Retinoschisis - Gehrke, Ella J.; Pandey, Araniko; Thompson, Jacob; Bhattarai, Sajag; Gurung, Prajwal; Hsu, Ying; Drack, Arlene V. (Frontiers in Medicine, 2024)
Purpose: Previous studies have reported Caspase-1 (Casp1) is upregulated in mouse models of Juvenile X-linked Retinoschisis (XLRS), however no functional role for Casp1 in disease progression has been identified. We performed electroretinogram (ERG) and standardized optical coherence tomography (OCT) in mice deficient in the Retinoschisin-1 (Rs1) and Casp1 and Caspase-11 (Casp11) genes (Rs1-KO;Casp1/11 -/-) to test the hypothesis that Casp1 may play a role in disease evolution and or severity of disease. Currently, no studies have ventured to investigate the longer-term effects of Casp1 on phenotypic severity and disease progression over time in XLRS, and specifically the effect on electroretinogram.Methods: Rs1-KO;Casp1/11 -/-mice were generated by breeding Rs1-KO mice with Casp1/11 -/- mice. OCT imaging was analyzed at 2-, 4-, and 15-16 months of age. Outer nuclear layer (ONL) thickness and adapted standardized cyst severity score were measured and averaged from 4 locations 500 µm from the optic nerve. Adapted standardized cyst severity score was 1: absent cysts, 2: <30 µm, 3: 30-49 µm, 4: 50-69 µm, 5: 70-99 µm, 6: >99 µm. Electroretinograms (ERG) were recorded in dark-adapted and light-adapted conditions at 2 and 4 months. Results obtained from Rs1-KO and Rs1-KO;Casp1/11 -/-eyes were compared with age matched WT control eyes at 2 months.Results: Intraretinal schisis was not observed on OCT in WT eyes, while schisis was apparent in most Rs1-KO and Rs1-KO;Casp1/11 -/-eyes at 2 and 4 months of age. There was no difference in the cyst severity score from 2 to 4 months of age, or ONL thickness from 2 to 16 months of age between Rs1-KO and Rs1-KO;Casp1/11 -/-eyes. ERG amplitudes were similarly reduced in Rs1-KO and Rs1-KO;Casp1/11 -/-compared to WT controls at 2 months of age, and there was no difference between Rs1-KO and Rs1-KO;Casp1/11 -/-eyes at 2 or 4 months of age, suggesting no impact on the electrical function of photoreceptors over time in the absence of Casp1.Although Casp1 has been reported to be significantly upregulated in Rs1-KO mice, our preliminary data suggest that removing Casp1/11 does not modulate photoreceptor electrical function or alter the trajectory of the retinal architecture over time.